1990
DOI: 10.1177/009102609001900309
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Rights Arbitrator Willingness to Accept Public Sector Interest Arbitration Cases

Abstract: A model is proposed to explain rights arbitrator willingness to accept interest arbitration cases. Findings suggest that rights arbitrators are more likely to accept interest arbitration cases if they are younger, they are not a NAA member, they have strong beliefs in their ability to render interest arbitration decisions, and they have more experience handling interest arbitration cases. The proposed model accounted for just under half the variance (Adjusted R2 = 0.48) in rights arbitrator willingness to acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As union membership in the public sector has grown, the spread of collective bargaining has created an increased reliance on arbitration (Vest, O'Brien, and Vest, 1990). The study examines the last step of the grievance process--arbitration.…”
Section: Grievance Arbitration In the Public Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…As union membership in the public sector has grown, the spread of collective bargaining has created an increased reliance on arbitration (Vest, O'Brien, and Vest, 1990). The study examines the last step of the grievance process--arbitration.…”
Section: Grievance Arbitration In the Public Sectormentioning
confidence: 99%
“…Although the empirical research on grievance arbitration in the public domain is scarce, recent literature does provide some empirical evidence supportmg the distinctive nature of arbitration in the public domain (e.g., Katz and LaVan, 1991;LaVan, 1993;LaVan, Katz, Sendelbach, and Stonebraker, 1987;Magnusen and Renovitch;1989;Rueschhoff, 1991;Stewart and Davy, 1992;Vest, O'Brien, and Vest, 1990). In a series of studies conducted by LaVan and her colleagues, significant differences were found between public and private sector arbitration cases.…”
Section: Grievance Arbitration In the Public Sector: A Literature Reviewmentioning
confidence: 99%
“…More than one-third of state government employees belong to unions as do almost one-half of people employed by local governments and schools (Coleman, 1990). Ac companying this growth has been the spread of collective bargaining into the public sector and an increased reliance on arbitration (Vest, O'Brien, & Vest, 1990). Many states have passed legislation mandating arbitration and have given arbitrators sole responsibility for settling collective bargaining agreement disputes with binding arbitration provisions (Coleman, 1990;Dunn & Overton, 1988).…”
mentioning
confidence: 99%